PENGARUH PROFITABILITAS, LEVERAGE, DAN ARUS KAS BEBAS TERHADAP KEBIJAKAN DEVIDEN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASIAN - Andriyanti, Lina; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2014)
The purpose of this study was to determine the effect of profitability, leverage, and free cash flow to dividend policy with good corporate governance as a variable pemoderasian. The results of hypothesis testing showed profitability, leverage, and free cash flow does not significantly influence the dividend policy. This study proves that good corporate governance is not able to moderate the relationship between profitability and dividend policy, leverage the relationship between dividend policy, and the relationship between free cash flow to the dividend policy.
Keywords: Profitability, Leverage, Free Cash Flow, Dividend Policy, Good Corporate Governance